Dissent a subtle reflection in opposition against Anwar - Daily Express, (KK) (Daily Express (KK), 2013)
KUALA LUMPUR:The actions of several Pakatan Rakyat leaders in disagreeing with the desire of pro opposition groups to topple the Barisan Nasional (BN) government through street demonstrations and violence have indirectly rejected PKR de facto leader Datuk Seri Anwar Ibrahim say political analysts.